Creative Solutions: An Art-Based Intervention to Address Burnout in CAMHS - Amelia Smith; Erica Pietrogrande (BJPsych Open)
Aims: Workplace stress and burnout are common within healthcare. The NHS Staff Survey 2023 found that approximately one third of respondents were experiencing burnout and were considering leaving the organisation. Studies suggest this is significantly higher in Child and Adolescent Mental Health Services (CAMHS). The negative impact of burnout on staff wellbeing, retainment, and patient care is well-recognised. Arts-based interventions have been shown to improve work-related stress and promote empathy and resilience. We set up a regular reflective art group for staff at an adolescent mental health team to see if this would reduce stress and improve wellbeing and job satisfaction.